Ergonomic assessment for the task of repairing computers in a manufacturing company: A case study. - Maldonado-Macías, Aidé; Realyvásquez, Arturo; Hernández, Juan Luis; García-Alcaraz, Jorge (Work, 2015)
BACKGROUND: Manufacturing industry workers who repair computers may be exposed to ergonomic risk factors. OBJECTIVES: This project analyzes the tasks involved in the computer repair process to (1) find the risk level for musculoskeletal disorders (MSDs) and (2) propose ergonomic interventions to address any ergonomic issues. METHODS: Work procedures and main body postures were video recorded and analyzed using task analysis, the Rapid Entire Body Assessment (REBA) postural method, and biomechanical analysis. RESULTS: High risk for MSDs was found on every subtask using REBA. Although biomechanical analysis found an acceptable mass center displacement during tasks, a hazardous level of compression on the lower back during computer's transportation was detected. CONCLUSIONS: This assessment found ergonomic risks mainly in the trunk, arm/forearm, and legs; the neck and hand/wrist were also compromised. Opportunities for ergonomic analyses and interventions in the design and execution of computer repair tasks are discussed.